The Role of Abnormal Tibiofemoral Rotation in Pediatric and Adolescent Patellar Instability. Issue 7 (30th July 2018) - Bernholt, David; Lamplot, Joseph D.; Eutsler, Eric; Nepple, Jeffrey J.
Objectives: Abnormal patellofemoral tracking has been implicated in patellar instability and can be influenced by the bony anatomy and alignment of the femoral trochlea, patella, and tibial tubercle. Tibiofemoral joint rotation has been recently suggested to play a role in patellofemoral kinematics but there has been little investigation of its contribution to patellar instability, including in pediatric and adolescent patients. Methods: A retrospective case-control design was utilized. 30 patients aged 9-18 with a prior patellar dislocation and an MRI of the involved knee were included. Cases were matched for age and gender with controls without patellar instability. Patients with ACL tears, tibial eminence or tubercle fractures, or prior surgery in the involved extremity were excluded. There was no difference in gender, age, height, but BMI was higher in the case group. MRI images taken with knee in extension were analyzed. Tibial tubercle-trochlear groove (TT-TG), tibial tubercle-posterior cruciate ligament (TT-PCL), and tibiofemoral rotation were measured. All measurements were performed by a single reader with excellent intra and interobserver reliability for tibiofemoral rotation (ICC-intra > .954 and ICC-inter > .905) demonstrated in a subset of patients. Results: The TT-TG was increased in patients with patellar instability at 16.3 mm compared to 10.9 mm in controls (p <.001) as was also the TT-PCL at 19.4 mm cases versus 17.6 mm (p=0.02). Tibiofemoral rotation was increased in patients with patellar instability with a mean 6.9° of tibial external rotation compared to 0.8° of tibial internal rotation in controls (p < .001). Overall, 30/41 (75.6%) of patients with patellar instability had tibiofemoral rotation >5° external rotation versus only 3/41 controls (7.3%). There was a strong correlation between TT-TG and tibiofemoral rotation (PCC = 0.776) and a moderate correlation between TT-TG and TT-PCL (PCC = .661). There was only a weak correlation between tibiofemoral rotation and TT-PCL. Conclusion: Increased tibiofemoral rotation is present in patients with patellar instability and may play a role in the pathophysiology of patellar instability. Increased tibiofemoral rotation can lead to an increased TT-TG even when TT-PCL is normal.